Arah dan Kecepatan Aliran Air Tanah Calon Tapak Disposal Demo di Kawasan Nuklir Serpong - Sucipta, Sucipta; Setiawan, Risdiyana (EKSPLORIUM, 2016)
Plan for construction and operation of demo disposal facility in Serpong Nuclear Area requires safety assessments to provide scientific evidence that the facility is safe for human and the environment. The result of the safety assessment is used also as a basis for granting environmental permits for the construction and operation of the facility. One of the site data requirements on the safety assessment is the direction and velocity of groundwater flow. Therefore, a study to determine the direction and velocity of groundwater flow at lower zone aquifer of demo disposal site candidate in Serpong Nuclear Area conducted. The research was carried out by using Rhodamin WT tracer. The tracer released in the main well (SBU) and monitored in SBP-1 (A), SBP-2 (B), and SBP-3 (C) boreholes. Based on the water samples and spatial analysis, groundwater data flow direction at a depth of 16 m towards N 240º E (west-southwest) with a velocity of 0.35 m/day up to 0.48 m/day obtained.